Limitation of Non-Halal Income (Interest) in the Criteria of Sharia Securities List in Indonesia Stock Exchange - M Fatchurrohman; Pungky Lela Saputri (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The Islamic capital markets in Indonesia have been developing over the last two decades, characterized by an increase in Islamic products and the issuance of regulations related to the Islamic capital markets, and the general public and investors are beginning to understand the list of Islamic securities. Next, there is one of the controversial criteria for the Sharia Securities List. That is, the total yield is less than 10%. It is understandable whether Islamic financial institutions earn income from bank interest before they are fully subject to Sharia law. This study analyzes the dispute using an associative approach by building relationships between social situations or domains based on the interdependencies of the dispute under study. It is a study to do. The results of this survey and discussion are based on an analysis of non-Halal income (interest) restrictions in the criteria for listing Shariah securities in Indonesia to address the conditions, risks and possibilities of DES. When the interest rate floor applies, few Shariah stocks need to be listed on flat Islamic securities and DES market shares, reducing interest in investing in the Islamic capital markets. This is also related to including other Shariah financial institutions. If the number of Islamic issuers decreases, the number of investors will surely decrease. Therefore, it will certainly be difficult to achieve in the development of the Islamic financial industry.